2023
DOI: 10.1021/acsphotonics.2c01622
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-Power Cryogenic Thermometry Based on Optical-Transition Broadening of a Two-Level System in Diamond

Abstract: Cryogenic temperatures are the prerequisite for many advanced scientific applications and technologies. The accurate determination of temperature in this range and at the submicrometer scale is, however, nontrivial. This is due to the fact that temperature reading in cryogenic conditions can be inaccurate due to optically induced heating. Here, we present an ultralowpower, optical thermometry technique that operates at cryogenic temperatures. The technique exploits the temperature-dependent linewidth broadenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…An example of a fitted spectrum is shown in Supporting Information Figure S2. The second-order autocorrelation measurements were conducted with the Hanbury Brown–Twiss setup equipped with two SPAPDs and a time-correlated single-photon counting module (Time Tagger 20) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of a fitted spectrum is shown in Supporting Information Figure S2. The second-order autocorrelation measurements were conducted with the Hanbury Brown–Twiss setup equipped with two SPAPDs and a time-correlated single-photon counting module (Time Tagger 20) …”
Section: Methodsmentioning
confidence: 99%
“…The secondorder autocorrelation measurements were conducted with the Hanbury Brown−Twiss setup equipped with two SPAPDs and a time-correlated single-photon counting module (Time Tagger 20). 31 Structural Characterization. Atomic Force Microscopy.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Temperatures below 120 K are generally considered cryogenic, where research pertaining to the study of superconductivity, aerospace materials, and quantum devices often occurs. Contact-based thermometry measurements for cryogenic systems can pose particular challenges due to the often-unavoidable heat transfer between the relatively hot probe and a cold sample. As a result, a variety of luminescent thermometers have been developed specifically for cryogenic thermometry.…”
Section: Capabilitiesmentioning
confidence: 99%
“…Fukami et al utilized the ZPL amplitude ratio of NV centers in nanodiamonds at temperatures ranging from 85 to 300 K. Across the cryogenic range, an important cutoff exists at 77 K, where liquid nitrogen cooling systems reach their lower temperature limit. Below this limit, helium-cooled systems are necessary as demonstrated by Chen et al, who used the temperature-dependent line width of GeV centers in nanodiamonds for thermometry from 5 to 35 K. Additional work in the ultralow temperature range was performed by Zhao et al, who demonstrated a Tb 3+ /Eu 3+ MOF thermometer with tunable relative sensitivity for the 25 to 125 K range. A similar temperature range of 40 to 150 K was achieved using the ratiometric response from the thermally coupled 4 T 2 to 4 A 2 and 2 E to 4 A 2 transitions of Cr 3+ in a CaHfO 3 perovskite host .…”
Section: Capabilitiesmentioning
confidence: 99%
“…16 group IV color centers such as germanium-vacancy (GeV), silicon-vacancy (SiV), lead-vacancy, tin-vacancy, etc., are some of the most common diamond color centers, owing to their compelling photophysical properties. 17 Temperature changes alter various spectral characteristics of diamond color centers, such as zero phonon line (ZPL) wavelength, 18 ZPL line width, 19 photoluminescence (PL) intensity, 20 shift in optically detected magnetic resonance (ODMR) spectra, 21 etc., which are then analyzed to set up the correlation between the observable and temperature. However, most of these methods require postprocessing of the acquired data or take a longer time to acquire spectral features, which can lead to slower temperature measurements.…”
Section: Introductionmentioning
confidence: 99%